PERAN ELIT STRATEGIS DESA DALAM PENYELESAIAN KONFLIK TANAH ULAYAT ANTARA MASYARAKAT DENGAN PTPN V DI DESA SENAMA NENEK KECAMATAN TAPUNG HULU KABUPATEN KAMPAR TAHUN 2016 – 2019 - Rafiqatul Aulia; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The role of the village strategic elite who are representatives of the Indigenous people in Kenegerian Senama Nenek, Tapung Hulu District, Kampar Regency, is very serious in resolving the ulayat land conflict with PTPN V, which has been going on for a long time since 1996. From 1996 the community demanded that PTPV V return 2,800 ha of land to them. villagers. Ninik mamak and the village government are at the forefront of resolving this conflict. They made various efforts in fighting for community customary land, both in uniting community opinions in dealing with PTPN V and meeting government agencies to get support, both from the sub-district level to the DPPR RI level. It was only in 2019 that it was decided directly by President Jokowi, that the 2,800 ha of land would be returned to the people of Senama Nenek Village. Based on this background, it is necessary to investigate the settlement of customary rights land disputes between the indigenous peoples of Senama Grandma and PTPN V. The research approach used is a qualitative approach. This type of research is descriptive. The research location is in Senama Nenek Village, Tapung Hulu District, Kampar Regency. Types and sources of research data are divided into primary and secondary data with data collection techniques through interviews and secondary data in the form of supporting data related to conflict. The results of this study are that the role of the strategic elite of Senama Nenek Village in fighting for the customary land area of 2,800 ha from PTPN V has been full of struggle for quite a long time. The settlement of land conflicts in the village of Senama Nenek which was carried out by the ninik mamak and the Village Government with negotiations between the Senama Nenek village community and PTPN V which resulted in a decision that PTPN V must find a replacement land area of 2,800 ha, mediation, namely by holding meetings between the community Senama Nenek and the Company were mediated by the DPD, Ombudsman, Komnas HAM, and the Regional Government and Arbitration, namely by involving third parties to resolve land conflicts in the village of Senama Nenek. Keywords: Conflict, Negotiation, Mediation, Arbitration